Decentralization, Subjective Well-Being And The Perception Of Institutions - Luis Diaz-Serrano; Andrés Rodríguez-Pose (European Regional Science Association (ERSA), 2012)
This paper analyses whether the different powers and resources at the disposal of local and regional governments across Europe deliver greater satisfaction with political institutions and lead to greater personal happiness. The analysis uses microdata from the four available waves of the European social survey (2002, 2004, 2006 and 2008), including more than 160,000 observations of individuals living in 29 European countries. Our results reveal that fiscal and some forms of political decentralization have a positive and significant effect on the overall subjective well-being of individuals. However, fiscal decentralization has a different effect on the perception of institutions depending on whether we consider subnational expenditure or revenues. Similarly, the effect of political decentralization on the level of satisfaction with institutions also varies depending on whether the capacity of local governments to influence national politics or to exert authority over their own citizens is considered. The results also show that citizens seem to be happier with the actual capacity of their local governments to deliver than with the general principle that they can have a say on their daily politics and policies.
Keywords: H11; H77; 330; Happiness; subjective well-being; satisfaction; fiscal and political decentralization; Europe